2007
DOI: 10.1002/jat.1309
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of jet fuel aliphatic hydrocarbon induced toxicity in human epidermal keratinocytes

Abstract: Jet propellant (JP)-8, the primary jet fuel used by the U.S. military, consists of hydrocarbon-rich kerosene base commercial jet fuel (Jet-A) plus additives DC1-4A, Stadis 450 and diethylene glycol monomethyl ether. Human epidermal keratinocytes (HEK) were exposed to JP-8, aliphatic hydrocarbon (HC) fuel S-8 and aliphatic HC pentadecane (penta), tetradecane (tetra), tridecane (tri) and undecane (un) for 5 min. Additional studies were conducted with signal transduction pathway blockers parthenolide (P; 3.0 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…3B), COX-2, and/ or immune suppression (Ramos et al, 2007) when we used synthetic jet fuel (S-8), which is devoid of aromatic hydrocarbons. Others however, have demonstrated that treating cultured human epidermal keratinocytes with S-8 induces the production of the inflammatory cytokines IL-6 and IL-8, and JP-8 INDUCES COX-2 VIA ROS AND NF-jb that cytokine production can be inhibited by parthenolide, implying a role for NF-jb (Inman et al, 2008). We suggest that the differences between our results and those reported by Inman and colleagues could be attributed to a number of factors.…”
Section: Discussioncontrasting
confidence: 72%
“…3B), COX-2, and/ or immune suppression (Ramos et al, 2007) when we used synthetic jet fuel (S-8), which is devoid of aromatic hydrocarbons. Others however, have demonstrated that treating cultured human epidermal keratinocytes with S-8 induces the production of the inflammatory cytokines IL-6 and IL-8, and JP-8 INDUCES COX-2 VIA ROS AND NF-jb that cytokine production can be inhibited by parthenolide, implying a role for NF-jb (Inman et al, 2008). We suggest that the differences between our results and those reported by Inman and colleagues could be attributed to a number of factors.…”
Section: Discussioncontrasting
confidence: 72%
“…These include an anti-icing agent (diethylene glycol monomethyl ether [DGME]), an antistatic agent (Stadis 450), and an anticorrosive agent (DCI-4A), all of which are required additives, while the addition of metal chelators and antioxidants is allowed but not required (Inman et al, 2008; Ritchie et al, 2003). According to the Air Force Logistics Management Agency, DGME is found in JP-8 at a 1:1000 dilution, while DCI-4A and Stadis 450 are present at smaller concentrations (1:66,660 and 1:666,666 dilutions, respectively) (AFLMA, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As we know, S-8, an aliphatic hydrocarbon (HC) fuel, is synthesized using the FT synthetic fuel process. Synthetic gas produced from natural gas, coal, or biomass is converted using heat and pressure into a clean burning liquid fuel made up of aliphatic HC (Inman et al, 2008). Its toxic effect may different with JP-8 due to its molecular weight, specific gravities, and compositions, with S-8 jet fuel containing alkane-rich hydrocarbons in the C7-C18 range and JP-8 jet fuel with aromatic hydrocarbons in the C9-C16 range.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that S-8 is devoid of aromatic hydrocarbons, S-8 may have the higher threshold level at which damage occurs when compared with that of JP-8 jet fuel. Two recent dermal exposure studies have provided solid support for this speculation (Ramos et al, 2007;Inman et al, 2008). One applied S-8 alone to the skin of mice did not upregulate the expression of epidermal cyclooxygenase-2 (COX-2) nor does it induce immune suppression (Ramos et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation